O impacto da corrupção no desenvolvimento dos brics: uma análise de efeito no desenvolvimento das firmas - Barreto, Adna Raquel de Morais (2019)
This paper aims to investigate the impact of corruption on the development of firms and, therefore, on the nations that form the BRICS where they are located. Economic and governance indicators are aggregated in this analysis, seeking to assess how each of these relate to and contribute to economic growth. By analyzing the results obtained from the study of correlations between indicators, it was possible to conclude that Corruption is more present in contexts where Government Efficiency, Regulatory Quality and Rule of Law are more absent and these, in turn, have a positive effect on firms' revenues while Corruption has the opposite effect. The estimation of an econometric model allowed us to observe that initially corruption can be a viable alternative for overcoming bureaucratic obstacles, inefficiency and institutional failures. However, when analyzing all the factors present in the scenario in which firms are inserted, it is possible to suggest that corruption does not facilitate development but leads to inefficiency within firms by diverting resources and efforts that begin to form barriers to growth.